2021
DOI: 10.3390/ijerph18073607
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study Regarding the Health Profile of the 2017 South African Hajj Pilgrims

Abstract: The Hajj mass gathering annually attracts over two million Muslim pilgrims worldwide to the Kingdom of Saudi Arabia (KSA). We aimed to establish demographics and health profiles for the South African pilgrims performing the 2017 Hajj. Methods: This is a longitudinal survey-based study conducted on 1138 adult South African pilgrims in two phases (during and post-Hajj). Data on demographics, vaccination status, underlying health conditions, pre-Hajj training, health promotion, travel history, and health issues d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…Prior to making the Hajj, several vaccinations and vitamin boosters were recommended. Symptom‐based medications as prescribed were allowed with their proper use (Farahmand et al., 2022; Mushi et al., 2021). Health‐risk assessment and management, including technology‐based disease monitoring were included in the current trends regarding protecting their health status (Pane et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to making the Hajj, several vaccinations and vitamin boosters were recommended. Symptom‐based medications as prescribed were allowed with their proper use (Farahmand et al., 2022; Mushi et al., 2021). Health‐risk assessment and management, including technology‐based disease monitoring were included in the current trends regarding protecting their health status (Pane et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A few studies reported the incidence of death as only 13.89% in this review. There was an incidence rate of about 44 deaths The most common communicable disease during the Islamic pilgrimage to Mecca was respiratory tract infection (Alasmari et al, 2020;Farahmand et al, 2022;Mushi et al, 2021). This was followed by several ambiguous infectious symptoms such as cough, fever, and sore throat.…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to the 2017 study where the prevalence of illnesses or injuries amongst South African Hajj pilgrims was recorded as 65.1%, of which 70.2% of presentations were respiratory conditions. 6 The prevalence of respiratory symptoms was reported as high as 77.6% amongst Iranian pilgrims, 15 in excess of 47.0% in 2016 amongst Indian pilgrims 2 and a reported 95.2% in a cohort of 394 Malaysian pilgrims. 16 Our findings are suggestive of the positive effect of exercise on improving immune function and stress resistance and thereby reducing susceptibility to respiratory infections.…”
Section: Discussionmentioning
confidence: 97%
“…Pre-existing medical conditions in our study was 34% which is similar to the prevalence described in other studies. 6 The co-morbidities, together with the harsh environmental conditions and large crowds, place these pilgrims at increased risk of developing community acquired pneumonias and invasive pneumococcal disease. 14 In the current study only 13 (14.7%) of participants suffered illness or injury with 6 (46.2% of presentations) reporting respiratory conditions during Hajj.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation